IoT-Based Monitoring of Solar Panel Current and Voltage - Burhannudin Yusuf Habibie; setyo - supratno; Sugeng Sugeng (Universitas Telkom, 2024)
Conventional monitoring systems have several weaknesses, including limitations in acquiring real-time physical parameters, which impact performance. Additionally, human errors often hinder data quality, further compounded by the inability to respond swiftly to rapid changes in physical parameters due to diverse operating conditions. To address these challenges, an innovative method has been developedfor solar panelcurrent and voltage monitoring using Internet of Things (IoT) technology. This system relies on the NodeMCU ESP8266 microcontroller and the INA219 sensor to monitor the current and voltage of the solar power system. Data obtained by the sensor is collected in real-time, stored in a cloud-based database, and visualized through a web platform. This allows users to monitor the system remotely andaccess solar panelperformance information. Measurements indicate that discrepancies between manual and web-based data are within 2%.The average manual readings of PV voltage and current are 16.96 volts and 119.66 mA, while the web-based readings are 16.98 volts and 118.38 mA. The differences in voltage and current are 0.12% and 1.07%, respectively. The average battery voltage is recorded at 10.5 volts, while the DC motor load shows a voltage difference of 0.63% and a current difference of 1.15%. The battery power test also indicates a difference of 0.65%. This system is effective because it provides real-time access from any location, facilitates quick responses to anomalies, and supports maintenance planning by storing historical data.